The Watson-Crick rare tautomer hypothesis of mutations and reality - Kryachko, E. S. (Biophysical Bulletin, 2020)
Background: In their Nature’s seminal work (Nature. 1953;171:737), J.D. Watson and F.H.C. Crick noted that the structure of DNA admits a so-called tautomeric model of spontaneous point mutations. This work reported at the conference "Nanobiophysics-2019" (Kiev) as a plenary report, is actually an attempt to answer the following questions: (i) "Yes, the tautomerism of the bases is a very attractive model, but how important is it in mutagenesis?" by Morgan (Morgan AR. Trends Biochem. Sci. 1993;18:160–163); (ii) What reality does the rare tautomeric mutation model describe? The structure [А×Т]WC was selected in the work. Developing the previously proposed mutation model×of the Watson-Crick pair [А×Т]WC due to the shift of the bases in the pair relative to each other and the interconnection hydrogen bonds (Kryachko ES, Sabin JR. Int. J. Quantum Chem. 2003;91:695–710), it is shown that some resultant structures possess the electron affinity that is 1.7 times higher compared to the canonical pair, which is definitely of interest in the view of the numerous phenomena associated with a charge transfer in and attachment of an electron to DNA. Objectives: Answer the questions raised in the Background, and show the realism of the tautomeric [А×Т]WC-mutation model modified in the present work on the example of the Watson-Crick pair [А×Т]WC that is dubbed as a pair-tautomerism model. Materials and Methods: The key method is a computer simulation based on the density functional method. All calculations performed in the present work use the package of programs GAUSSIAN with the density functional method invoking the Becke-Lee-Yang-Parr density functional, B3LYP. Results: The paper shows the existence and stability of paired tautomeric mutations in a pair of adenine-thymine and investigates to what wobble pairs it can lead. It is also shown that, due to the specific structure of the paired tautomeric mutation of the adenine-thymine pair, the mutation possesses a larger electronic affinity in comparison with the pair that it generates, and thus can be observed in reality and through it one can explain a number of phenomena of charge transfer in DNA, which, again, emphasizes its reality. Conclusions: On the one hand, a generalization of the Watson-Crick tautomeric hypothesis, proposed in this work, specifically for the adenine-thymine pair, the name of the paired tautomeric mutation. This mutation refers to dipole-binding-electron systems, which implies their high adiabatic electron affinity. The latter, on the other hand, emphasizes the realism of the proposed mutational model and its possible application to the explanation of the phenomena of charge transfer in DNA and the processes of attachment electron to DNA.